PENERAPAN PENDIDIKAN KARAKTER PADA SISWA SD MASA PANDEMI COVID-19 - Nur Samsiyah; Ririn Nuryanti; Endang Sri Maruti (PEDIR: Journal of Elementary Education, 2021)
This study aims to explain the application of character education to students of SDN Taman 01 Madiun City. This research was conducted during the Covid-19 pandemic. This indicator is a form of character education while studying at home carried out by students starting from maintaining the cleanliness of themselves, the environment, society and applying it in everyday life. Data were collected by observation and interviews and through social media. The sources of this research are educators, students, teachers and parents. The results show that the application of character education is not only in learning but the real practice carried out by students such as caring for the environment, creative character and innovation, responsibility and social. Students who have the character of caring for the environment by participating in maintaining a clean environment by inviting others to always obey environmental health protocols.